Novel strategy for dental caries by physiologic dentin regeneration with CPNE7 peptide. (November 2022) - Gug, Hye Ri; Park, Yeoung-Hyun; Park, Su-Jin; Jang, Ji Yeon; Lee, Ji-Hyun; Lee, Dong-Seol; Shon, Won-Jun; Park, Joo-Cheol
Abstract: Objective: CPNE7-derived functional peptide (CPNE7-DP) has been introduced as a bioactive therapeutics for dentin diseases. CPNE7-DP regenerates tubular dentin on the pulpal side and occlude dentinal tubules. CPNE7-DP was capable to treat dentin hypersensitivity typically associated with dentinal wear at the neck of the tooth. However, the role of CPNE7-DP in another common dentin disease, dental caries, remains uninvestigated. In this study, we evaluated the potential application of CPNE7-DP in dentin caries using an experimental dentin caries model in rats. Design: The stability of CPNE7-DP in caries-like environments including pathologic bacteria of caries or low pH was tested. We established a nutrition-time/hyposalivation-based dental caries rat model by inoculating caries-inducing bacteria and diet for sufficient time. Glycopyrrolate has been treated to induce reversible hyposalivation for accelerating caries progression. Then the tubular dentin regeneration was investigated with histologic methods. Also, modulation of inflammation or autophagy by CPNE7-DP was investigated with marker gene expression in human dental pulp cells (hDPCs) and immunohistochemistry. Results: CPNE7-DP was stable with caries-inducing bacteria and low pH. Establishment of dentin caries was confirmed with radiographic and histologic evaluation. CPNE7-DP regenerated a substantial amount of tubular tertiary dentin and alleviated the pulp inflammation of dentin caries. Under inflammatory conditions, CPNE7-DP reduced the expression of inflammatory cytokines. These phenomena could be the consequence of the modulation of autophagy by CPNE7-DP, which reactivates inflamed odontoblasts. Conclusions: Overall, CPNE7-DP, which repairs caries through physiological dentin regeneration, might help overcoming the limitations of current restorative caries treatments. Graphical Abstract: ga1 Highlights: CPNE7-DP produced tubular dentin and alleviated pulpitis in carious lesions. Preserved dentin thickness with tubule occlusion delayed the pulpitis progression. CPNE7-DP showed potential as a bioactive agent for minimally invasive dentistry. This could help patients with difficulties in caries treatment such as pediatrics.